Pre-immunotherapy radiotherapy enhanced the efficacy of multi-line sintilimab in unresectable advanced esophageal squamous cell carcinoma - Xu, Shuhui; Xu, Xianxing; Zhu, Hui (Frontiers in Immunology, 2023)
Background: The use of immunotherapy for the treatment of esophageal squamous cell carcinoma (ESCC) is gradually increasing. In this retrospective study, we evaluated the efficacy and explored potential factors of prognosis in multi-line sintilimab for unresectable advanced ESCC. Methods: All pathological specimens were available from our Department of Pathology. We performed PD-L1 immunohistochemical staining of surgical or puncture specimens from 133 patients. We evaluated the efficacy of multi-line sintilimab and found potential factors according to multivariate analysis. The relationship between the radiotherapy and immunotherapy was assessed, and according to whether patients had received radiotherapy within 3 months prior to immunotherapy, we attempted to analyse differences in PFS and OS. Results: A grand total of 133 patients were enrolled in this retrospective study between January 2019 and December 2021. The median follow-up was 16.1 months. All patients were treated with at least two cycles of sintilimab. Of all patients, a total of 74 experienced disease progression, with a median progression-free survival of 9.0 months (95% CI 7.701-10.299). We found that pre-immunotherapy radiotherapy was a possible predictor that affected the prognosis of multi-line sintilimab and 3 months was a significant cut-off. A total of 128 patients (96.2%) had received radiotherapy prior to immunotherapy. Of those patients, 89 (66.9%) had received radiation therapy within 3 months prior to immunotherapy. PFS was considerably longer in patients who were treated within 3 months radiotherapy than in patients who had not received radiation therapy within 3 months of radiation therapy prior to immunotherapy (median progression-free survival 10.0 months [95% CI 8.030-11.970] vs. 5.0 months [95% CI 2.755-7.245]). Among all patients, the median overall survival was 14.9 months (95% CI 12.558-17.242). Overall survival was significantly longer in patients who had previously received radiotherapy within 3 months prior to immunotherapy than in those who had not (median overall survival 15.3 months [95% CI 13.724-16.876] vs. 12.2 months [10.001-14.399]. Conclusion: Based on this retrospective study, sintilimab is a significant option for previously treated patients with unresectable advanced ESCC and pre-immunotherapy radiotherapy within 3 months enhanced the efficacy.